A Study of Relationship between Thinking Style, Attitude towards ICT and Computer Confidence among Student Teachers - Bijoy K. Thomas (International Journal on Integrated Education, 2023)
Thinking, a very convoluted process is the mental phenomenon that is most difficult to elucidate or express in terms of complexity. Each individual's unique way of taking in and processing the information they encounter is their "thinking style." The present research study examines the relationship between student teachers' thinking styles, attitudes towards ICT and computer confidence among student teachers. The researcher in this study attempts to identify the thinking variables that may directly or indirectly affect students' attitudes towards ICT and computer confidence. Samples for this study have been taken from student teachers enrolled in Bachelor of Education in Mumbai region, Maharashtra, India. Information and communication technology are crucial in this knowledge era, especially regarding the educational journey. The capacity to think critically helps teachers use technology in the classroom for information creation, management, and distribution. The Thinking Style Inventory, established and standardized by Robert J. Sternberg in 1997, was used in this study to gather data on the thinking pattern of student teachers. The standardized questionnaire was developed by Nash, John B., and Moroz, Pauline A. (1997) to assess student teachers' attitudes towards ICT and computer confidence. The quantitative data were analyzed with the SPSS program. The findings indicate that a favourable attitude towards ICT may be attributed to enhanced computer confidence and the promotion open and creative thinking abilities. Student educators should gain positive technological experience.